A ring of endless light - L'Engle, Madeleine (New York : Dell Laurel-Leaf, 1995)
Fifteen-year-old Vicky Austin spends a difficult summer as three young men vie for her attention at the same time that her grandfather struggles with leukemia.
Newbery Medal/Honor.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Book Links (A.L.A.), November 1995.
Bulletin (Center for Children's books), April 2004.
Five Owls, September 1997.
Keywords: Death -- Fiction; Dolphins -- Fiction; Death -- Fiction; Dolphins -- Fiction